Authentication and Authorization Applications in 4G Networks - null, null; Dostálek, Libor (Univerzita obrany, 2015)
This contribution to discuss the possibility of strong authentication for applications running on mobile devices. It deals with the possibility of combining algorithm AKA with other authentication algorithms. Combination of two algorithms will be created strong multifactor authentication, which is suitable for applications demanding high secure authentication such as Internet banking or Internet access to the Government applications.
Autentifikace a autorizace v 4G sítích
Keywords: Authentication, Smart Card, Security, Strong Password Authentication, Mobile Application Authentication; Autentizace, Čipové karty, Bezpečnost, Silná autentizace heslem, Autetnizace mobilních aplikací